Bezpieczeństwo informacji i ochrona danych osobowych jako polityka publiczna – analiza wprowadzenia mechanizmów i uregulowań prawnych - Wojciechowski, Łukasz (Polityka i Społeczeństwo, 2020)
The article aims to provide a comprehensive account of the legal regulations and mechanisms for the protection of personal data in Poland. In the last few years, considerable attention has been paid to this subject, which results in the wide-ranging character of the issues examined. The author classifies, based on sectors, the protection of personal data as a public policy and justifies such classification through the use of, among other tools, an institutional and legal method and factor analysis. The conclusions of the article are based on the analysis of the Polish legislation on the protection of personal data as well as on the analysis of the practical implementation of the solutions in companies, government and self-government institutions. Based on the results, it can be concluded that the protection of personal data falls within the scope of the public policy. However, it is necessary to take into account that some of its elements must be assigned to the policy of a party.